Penggunaan Media E-Book Creator Untuk Meningkatkan Kemampuan Menulis Cerita Inspiratif Peserta Didik Kelas IX F SMP Negeri 1 Dayeuhkolot Kabupaten Bandung Semester Genap Tahun Pelajaran 2021-2022 - N. Ai Kusumawati (Continuous Education: Journal of Science and Research, 2022)
This research was conducted based on observations with fellow Indonesian language teachers for class IX at SMP Negeri 1 Dayeuhkolot, it turned out that the students' ability to write inspirational stories was still low. This condition is found especially in Class IX F. The problems of students in writing inspirational stories the writer wants to improve by using e-book creator learning media in the learning process of writing inspirational stories. The purpose of this study was to improve the quality of the learning process of writing inspirational stories for class IX F students of SMP Negeri 1 Dayeuhkolot using e-book creator media and to improve the quality of learning outcomes for writing inspirational stories for students of class IX F at SMP Negeri 1 Dayeuhkolot. This research took place at Dayeuhkolot 1 Public Middle School, Bandung Regency. The form of research is Classroom Action Research, namely action research conducted with the aim of improving the quality of learning practices in the classroom. Data collection techniques with observation/observations, tests, and questionnaires. The data that has been collected is analyzed by comparing the results of the actions in each cycle with predetermined indicators of success. The results of the study obtained that the use of e-book creator media can improve students' ability to write inspirational stories. This increase can be seen, at the beginning of the study the percentage of students completing 38%, Cycle I became 67%, and in Cycle II became 86%.